Efficacy and Tolerability of Amlodipine-Valsartan Compared to Amlodipine-Atenolol Combinations in Hypertensive Patients: A Prospective Comparative Study (Jalalabad Medical Journal, 2025)
Amlodipine-valsartan and amlodipine-atenolol combination therapies may be used in patients where blood pressure is not adequately controlled on either component monotherapy or as initial therapy in patients who are likely to need multiple drugs to achieve their blood pressure goals. Single-pill combinations of amlodipine-valsartan and amlodipine-atenolol are available in Bangladesh for the treatment of patients with hypertension. This trial was designed to determine the efficacy and tolerability of valsartan and atenolol when both were combined with the calcium channel blocker (CCB) amlodipine. Efficacy was assessed by the patient’s blood pressure reading and tolerability based on the patient’s complaints at each follow-up. This interventional, prospective, comparative study was conducted in the outpatient department (OPD) of cardiology in collaboration with the outpatient department of medicine of Sylhet M.A.G Osmani Medical College Hospital between January 2022 and October 2022. The study included 80 patients with essential hypertension resistant to 4 weeks of 5 mg of amlodipine. Blood pressure and pulse rate were measured at preinclusion, inclusion (One week), and after 4 weeks, 8 weeks and 12 weeks of active treatment with an amlodipine-valsartan combination (5/80 mg) and an amlodipine-atenolol combination (5/50 mg). From baseline to week 12, both systolic and diastolic blood pressure decreased significantly in the amlodipine-valsartan group (-21.82±0.17/ -16.82±1.78 mmHg; p